Representações sociais sobre o trabalho dos professores de educação infantil de professoras que atuam com crianças até três anos em instituições da rede municipal de educação de Maceió/AL - Santos, Carla Manuella de Oliveira (2011)
This research aims to investigate what the possible content and structure of social representations that of children up to three years develop and share about teaching. The study comes within the context of the institutions of municipal kindergarten in the city of Maceió, Alagoas , and is based on the perspective of social representations theory of Serge Moscovici, in its articulation with the Central Nucleus Theory (Abric, 2000).The objective is to understand what the social representations constructed by 67 teachers about their own work, through a questionnaire composed of three parts: word association containing four words inducing (daycare, preschool, child and teacher), a questionnaire with 30 questions organized in the form of a letter, with 13 open questions and 27 closed questions. The data were processed by the following software: Programmes Permetettant Ensemble l'Analyse (EVOC) for analysis of evocations; Statistical Package for Social Sciences (SPSS) for treatment of closed questions, and Contexte d'Analyse Lexicale pair of one Esemble segments of Texte (ALCESTE), used for processing of the open questions the results for the word association test indicated that the representational field of nursery and pre-school, there is an emphasis on the dichotomy between care and education, which, according to the subjects of this research, attest distinct functions for these substeps of Early Childhood Education.Concerning this realization, the results of the representational field of child and teacher confer stability to the representation of the group studied, ie, bring elements with content that establish a child who resides at the level of feelings and protection. This requires personal skills, indicating that the competence or the ability to work as a teacher of very young children in day care is based on personal skills. For the results of the questionnaire letter, the teachers indicate that they know very little about what actually should be done with children as small, indicating that training did not include specifics for the job.The teachers show a job that requires, above all, patience, dynamism, and like children, however we realize that teachers also seek to "break" with the idea that, to work with children, just having personal skills. This is verified from a consensus established by the teachers to the impositions of the "other" (parents, friends, management, society) to indicate that specific training is essential and that teaching with young children demand particularities and specificities.This study provided a better understanding of the structure and dynamics of social representations that condition and often limit teachers' work with children up to three years, so that may contribute to the improvement of actions aimed at training teachers in Early Childhood Education.It is hoped that these professionals can understand the specifics of this stage of basic education and the peculiarities of educational action-oriented teaching the age group of zero to three years.